Zapowiedzi przedmałżeńskie a prawo do ochrony danych osobowych - Janczewski, Zbigniew (Ius Matrimoniale, 2007)
The publication of marriage banns was in the Church from the beginning of its activity. In the middle century IV Lateran Council commanded to publish da ta base of parties before contract marriage. Now Code of C anon Low prescribes: „Before a marriage takes place, it must be established that nothing stands in the way of its valid and lawful celebration”. „The Episcopal Conference is to lay down norms c o n c e rn in g . the publication of marriage b a n n s . ”. The Polish Episcopal conference in the year 1989 promulgated norms about preparation for entering marriage. Those norms order to publication of marriage banns in Poland. In the y ear 1995 polish Parliament passed a bill Personal Da ta Base Protection Statute. This document prohibits inter alia divulgation of news personal da ta bases. What can do a priests in those situation? The Concordat between Holy See and Republic of Poland decides that Catholic Church exercises jurisdiction according to canon low. Furthermore Personal Data Base Protection Statute permits data bases processing of people who are faithful of the Church.